Breaking bread!. Issue 1 (16th October 2018) - Rej, Anupam; Aziz, Imran; Sanders, David Surendran
Abstract : Humankind has existed for 2·5 million years but only in the past 10 000 years have we been exposed to wheat. Therefore, it could be considered that wheat (gluten) is a novel introduction to humankind's diet! Prior to 1939, the rationing system had already been devised. This led to an imperative to try to increase agricultural production. Thus, it was agreed in 1941 that there was a need to establish a Nutrition Society. The very roots of the Society were geared towards necessarily increasing the production of wheat. This goal was achieved and by the end of the 20th century, global wheat output had expanded by 5-fold. Perhaps, as a result, the epidemiology of coeliac disease (CD) or gluten sensitive enteropathy has changed. CD now affects 1 % or more of all adults. Despite this, delays in diagnosis are common, for every adult patient diagnosed approximately three–four cases are undetected. This review explores humankind's relationship with gluten, wheat chemistry, the rising prevalence of modern CD and the new entity of non-coeliac gluten or wheat sensitivity. The nutritional interventions of a low fermentable oligo-, di- and mono-saccharides and polyols diet and gluten-free diet (GFD) for irritable bowel syndrome and the evidence to support this approach (including our own published work) are also reviewed. There appears to be a rising interest in the GFD as a 'lifestyler', 'free from' or 'clean eater' choice, causing concern. Restrictive diets may lead to potential nutritional implications, with long-term effects requiring further exploration.